Financial reporting quality, does regulatory changes matter? evidence from Nigeria - Kibiya, Muhammad Umar; Che Ahmad, Ayoib; Amran, Noor Afza (2016)
The aim of the study is to investigate the effect of revised Code of Corporate Governance 2011 for public companies in Nigeria and how these changes affect the quality of financial reporting in the non financial firms in Nigeria between 2010 and 2014.The study employed McNichols (2002) accrual quality measure on pooled panel data with 505 firm-year observations.The findings revealed that the revised code brought changes that impacted positively in providing effective mechanisms for monitoring and control which decreases earnings management practices that enhanced the quality of financial reports in Nigerian non financial listed firms.However, specific variables contribution in improving the quality of firms’ earnings were found to be inadequate in enhancing the quality of financial reports.Thus, mandatory disclosure of equity and financial expertise of shareholders representatives on the audit committee in the governance reports would improve oversight monitoring functions of the board and audit committee.